Prevalência de sarcopenia em idosos usuários da atenção básica - Ghisolfi, Patricia de Carli Tonial (2017)
Rapid aging of the population is accompanied by an increase in the number of chronic non-communicable diseases and geriatric syndromes such as sarcopenia, which is characterized by progressive and generalized loss of skeletal muscle mass associated with reduced strength and/or physical performance, which causes more falls, worse quality of life, functional disability and higher mortality. Objective: To evaluate the prevalence of sarcopenia in elderly users of primary care Methods: A cross-sectional study with elderly users of the primary health care network, residents of the city of Marau, Rio Grande do Sul, Brazil. 148 elderly people aged 65 years and over were interviewed through an individual interview in the eleven Family Health Strategies Of the municipality. The elderly were evaluated for the diagnosis of sarcopenia, involving the calculation of muscle mass, grip strength and walking speed; sociodemographic, anthropometric and nutritional variables. Nutritional status was evaluated through the Body Mass Index (BMI) and the Mini Nutritional Assessment (MNA). Results: Of the elderly (n = 148), 72.3% were female, mean age was 73.6 years (SD = 5.5), ranging from 65 to 89 years, 60.1% were married or in stable union, there was predominance of white color (82.4%) and 58.1% studied until elementary school. Of the elderly evaluated, 23.6% lived alone and 85.8% lived in their own homes. The prevalence of sarcopenia was 14.2%, and 47.3% of the elderly had low manual grip strength and 53.7% had an inadequate walking speed. Regarding BMI, 10.8% of the elderly were classified as underweight and 75% of these were diagnosed as sarcopenic. Sarcopenia was significantly associated with the highest age group (p = 0.046) and BMI (p <0.001). Conclusions: These results highlight the importance of the diagnosis of sarcopenia in basic care, together with the evaluation of the nutritional status of the elderly who use the public health system, aiming at maintaining the quality of life and favoring active aging.